Characterization by 1H NMR of glycosidic conformations in the tetramolecular complex formed by d(GGTTTTTGG). - Wang, Y (1991)
We have conducted two dimensional NOESY studies on the molecule d(G2T5G2) to characterize the structure of the tetramolecular complex previously identified by calorimetric and spectroscopic studies (1). Analysis of the NOE and exchange cross peaks observed in the NOESY spectra establishes the formation of structured conformations at low temperature (5 degrees C). Significantly, within each strand of these structured conformations, the G1 and G8 residues adopt syn glycosidic torsion angles, while the G2 and G9 residues adopt anti glycosidic torsion angles. Consequently, any structure proposed for the tetramolecular complex of d(G2T5G2) must have alternating G(syn) and G(anti) glycosidic torsion angles within each strand. The implications of this observation for potential structures of the tetramolecular complex of d(G2T5G2) are discussed.